Covid-19 and sport in the Asia Pacific region - Tan, T.-C.; Lee, J. W. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The Covid-19 pandemic and the sport industry in Asia-Pacific Without a doubt, Coronavirus is the main keyword that defines the socio-cultural and economic climate of 2020. Few areas in the world were immune from this global pandemic, and the global sport industry has also been severely affected by this viral disease (Ruihley and Li 2020). Covid-19 hit Wuhan in China in late 2019, then in early 2020 it spread to Daegu in South Korea. More than seven hundred passengers and crews on the Diamond Princess Ferry docked on the port of Yokohama in Japan were infected by Coronavirus. East Asia was the first region that suffered from this epidemic before WHO declared it a global pandemic. The professional baseball and football leagues in this area, which normally start their new seasons in March, had delayed their opening matches until the virus is under control. Additionally, the 2020 Tokyo Olympic Games was postponed until July 2021. After having severely disturbed the sporting calendar in East Asia in the first quarter of 2020, Covid-19 invaded the West. This was the moment the operation of the global sport industry from East Asia via Europe to North America stopped completely without knowing the timing of its resumption (BBC 2020).